Concealed Weapons, Ordinance No. 4 of The Charter and Ordinances of the City of Helena, § 1 (1883) - (:unkn) unknown (General Publisher, 1883)
No person shall in this city wear under his clothes, or concealed on or about his person, any pistol or revolver, except by special permission from the mayor; nor shall any person wear under his clothes, or concealed on or about his person, any slung shot, cross knuckles, knuckles of lead, brass or other metal, or any bowie knife, razor, billy, dirk, dirk-knife or dagger, or any knife resembling a bowie knife, or any other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED